Navigating Women-Oriented Legal Frameworks: A Critical Examination Of Laws Addressing Gender-Based Violence And Empowerment (Journal of Namibian Studies : History Politics Culture, 2023)
This study undertakes a comprehensive examination of legal frameworks designed to combat gender-based violence and advance women’s empowerment. Through a comprehensive analysis of the efficacy, vulnerabilities, and socio-cultural ramifications of these legislative structures, this research endeavor seeks to provide a valuable contribution to the continuing scholarly conversation pertaining to women's rights and the pursuit of gender parity. The study utilizes a multidisciplinary methodology, integrating legal analysis, socio-cultural inquiry, and policy assessment. Through an analysis of significant legislative measures, international agreements, and regional protocols, this study critically examines the development of legal frameworks that focus on the rights and empowerment of women at a worldwide level. Moreover, the study explores the difficulties faced throughout the execution stage, encompassing concerns related to enforcement, the availability of legal remedies, and societal opposition. A significant proportion of the research is focused on investigating the complex correlation between legal reforms and measurable consequences of empowerment. Through examining case studies and empirical evidence, this study evaluates the extent to which these legislative procedures have effectively resulted in improved circumstances for women. Specifically, it examines their impact on lowering instances of gender-based violence and strengthening women's socio-economic agency. Moreover, this article conducts a thorough analysis of the intersectionality between these legal frameworks and many socioeconomic issues, including but not limited to class, racism, and sexual orientation. The study promotes a more inclusive and complete approach to women's rights within legal contexts by emphasizing potential biases and limits. The present study enhances our comprehension of the effects of legal frameworks that focus on women's rights in relation to combating gender-based violence and promoting empowerment. By examining their positive attributes and limitations, the research establishes a foundation for well-informed policy suggestions and advocacy endeavours that strive to establish more resilient, fair, and culturally attuned legal frameworks to promote gender parity.